Tinjauan Yuridis Hak Royalti Sebagai Harta Bersama dalam Perkawinan - Maulidina, Alfi Dianti; Purwanto, Aldira Mara Ditta Caesar (Wajah Hukum, 2024)
There are two concepts regarding marital assets according to the legal system in Indonesia, namely in the form of personal assets and joint assets. The correlation between marital property and IPR includes the legal and economic relationship between joint ownership of certain assets and the protection of creative or innovative rights. This research was conducted using normative research methods using statutory, conceptual and case approaches. The purpose of this research is to find out the position of royalties as marital property according to marriage law in Indonesia and to find out about the legal measures that can be taken by the parties regarding royalty rights as marital property in the event of a divorce. The research show that Copyright is a material right, so it can be concluded that Royalties fall into the category of intangible movable objects. Royalties which are intangible movable objects have value as joint assets. Then, dispute resolution regarding joint assets can be carried out through litigation and non-litigation processes. In practice, the division of joint assets can usually be resolved amicably, but if there is no agreement it will result in a legal process involving filing a lawsuit with the Religious Court. In terms of the division of marital property, it is regulated in the Civil Code, Marriage Law, and the Compilation of Islamic Law and the judge's considerations are based on the value of justice.